The ballet in the development of the technique of rhythmic gymnastics in girls from 12 to 14 years old - Tapia Bonilla , Johanna Noemi; Nacevilla Ríos , Eduardo Santiago (SATHIRI, 2023)
A methodological guide of ballet classes was applied to improve the technique of rhythmic gymnastics which was applied during three months of work, finding as a result an improvement of 29.67% it is determined that the ballet is very important in the development of the technique in rhythmic gymnastics, to improve your body awareness as well as music - rhythm, acrobatics, balances, rotations and jumping elements that are evaluated periodically and at the level of competences, the study carried out is very important for the training of new gymnasts, because the ballet develops several skills that rhythmic gymnastics cannotg develop only with a daily training. The ballet methodological guide, proposes that ballet and rhythmic gymnastics work periodically and constantly to improve the training program in the Pichincha Sports Concentration from an early age.